222 EXPRESSION OF CRE-RESPONSE GENES IN BRAIN REGIONS AFTER CHRONIC MORPHINE EXPOSURE. (1st January 2005) - Baquir, B.; Tran, B.; Tripathi, P.; Farasat, S.; Friedman, T. C.; Lutfy, K.
Abstract : Objective: To determine whether the level of cAMP response element binding (CREB) protein will be altered after chronic morphine administration. Methods: Male C57BL/6 mice (30 g) were implanted (under the nape) with a 25 mg morphine or placebo pellet. Seven days later, mice were perfused and brains were removed, imbeded and sectioned (7 mm coronal sections) using a microtome. We focused on the nucleus accumbens, hypothalamus and ventral tegmental area (VTA) due to the relation of these brain regions to drug addiction. CREB-P immunostaining was done by the Vectastain kit using an anti-phospo-CREB antibody to determine regulation of the phosphorylated form of CREB. Results: Our preliminary findings show that morphine treated brains express higher CREB-P than control treated brains. Areas of up-regulation included the nucleus accumbens, hypothalamus and VTA. Conclusion: Our results indicate that CREB-P may be involved in the development of opiate addiction. Further studies are needed to focus on other brain regions in addition to the nucleus accumbens, the hypothalamus and the VTA to determine the role of these areas in drug addiction.